Identifying brand touchpoints to increase switching costs in the banking industry. Issue 3 (9th December 2019) - Sultan, Abdullah
Abstract : Purpose: The purpose of this paper is to study the effect of staged customer experiences on customer switching costs in the banking industry. Design/methodology/approach: Brand touchpoints in the banking industry are identified by exploratory research using focus group sessions with bank customers and staff and refined by exploratory factor analysis using an independent sample of bank customers to form the staged customer experience construct. The proposed research model is then validated by confirmatory factor analysis with an independent sample using structural equation modeling. Findings: Customer experience in the banking industry consists of four related but distinct stages (i.e. pre-touch, in-touch, post-touch and service failure). The first three stages have direct and indirect effects on switching costs that are partially mediated by relationship quality. Research limitations/implications: Customer experience is an industry-specific construct with complicated effects on switching costs. Thus, the staged customer experience construct should be examined in different industries and applications to understand its implications. Practical implications: Bank customers demand experiences that achieve desirable results in everyday situations and switch to other service providers easily if this demand is not met. Banks should focus on brand touchpoints that are both important to customers and increase switching costs to keep customers from defecting. Originality/value: This research expands upon findings in the customer experience literature by exploring factors that link staged customer experiences with switching costs in the banking industry. In addition, a paradox is identified in the staged customer experience model that requires managers' attention in order to design an effective customer experience strategy.